2015
DOI: 10.1007/s11999-014-3851-z
|View full text |Cite
|
Sign up to set email alerts
|

Does the Risk Assessment and Prediction Tool Predict Discharge Disposition After Joint Replacement?

Abstract: Background Payers of health services and policymakers place a major focus on cost containment in health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 13 publications
3
63
1
Order By: Relevance
“…The Risk Assessment and Prediction Tool (RAPT), developed by Oldmeadow at Alfred Hospital in Victoria in 2001, is utilized to predict the discharge destination after joint replacement surgery and helps align the expectations of patients after surgery. The accuracy of RAPT has been validated . Patients with scores below 6 usually require inpatient rehabilitation, while those who have RAPT score above 6 will usually be discharged directly home, and those with a RAPT score greater than 9 are most likely to go home on day 1 after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The Risk Assessment and Prediction Tool (RAPT), developed by Oldmeadow at Alfred Hospital in Victoria in 2001, is utilized to predict the discharge destination after joint replacement surgery and helps align the expectations of patients after surgery. The accuracy of RAPT has been validated . Patients with scores below 6 usually require inpatient rehabilitation, while those who have RAPT score above 6 will usually be discharged directly home, and those with a RAPT score greater than 9 are most likely to go home on day 1 after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Hansen et al used this tool to assess 3213 patients undergoing TJA from 2006 to 2011. They found predictive accuracy in 80% of THA patients and 77% of TKA patients [20].…”
Section: Predicting Discharge Disposition After Primary Total Joint Amentioning
confidence: 98%
“…67,68 Our studies provide tools for risk assessment and discharge planning. Although the recent literature recommends the use of the Risk Assessment and Prediction Tool (RAPT) together with medical factors and body mass index, 68,69 we concluded that simple performance-based measures are of additional value to these more conventional measures and tools for predicting recovery (Chapter 3) and hence optimal discharge timing and destination. Shorter LOS and less use of inpatient rehabilitation will reduce costs; total hospital costs for THA are about 10,000 euro in the Netherlands 70 and 1 day of inpatient rehabilitation costs about 250 euro and a 14-day stay about 3000 euro.…”
Section: Effectiveness On Inpatient Postoperative Physical Functioningmentioning
confidence: 96%
“…Although exercise programs have an important role in optimizing preoperative and postoperative functioning, their effectiveness is still limited. [24][25][26]68,69 Given the different barriers elderly individuals face in their recovery after THA, there are several gaps between the needs of elderly patients and current care pathways and research.…”
Section: Osteoarthritis and Total Hip Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation